2021
DOI: 10.3390/pr9020236
|View full text |Cite
|
Sign up to set email alerts
|

Technologies and Extraction Methods of Polyphenolic Compounds Derived from Pomegranate (Punica granatum) Peels. A Mini Review

Abstract: The interest in using plant by-product extracts as functional ingredients is continuously rising due to environmental and financial prospects. The development of new technologies has led to the achievement of aqueous extracts with high bioactivity that is preferable due to organic solvents nonuse. Recently, widely applied and emerging technologies, such as Simple Stirring, Pressure-Applied Extraction, Enzymatic Extraction, Ultrasound-Assisted Extraction, Pulsed Electric Fields, High Hydrostatic Pressure, Ohmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 88 publications
0
32
0
3
Order By: Relevance
“…It reduces the drawbacks of spectrophotometric methods, such as expensive chemicals, undefined reaction time, low precision, low sensitivity, and long sample preparation time. The oxidative stress of food and living organisms is measured using electrochemical methods [104,105], including cyclic voltammetry, differential pulse voltammetry, square wave voltammetry, and chronoamperometry [105]. The cyclic voltammetry method provides a wide range of information, such as the thermodynamics of the redox process and kinetics of heterogeneous electron transfer reactions [104].…”
Section: Electrochemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces the drawbacks of spectrophotometric methods, such as expensive chemicals, undefined reaction time, low precision, low sensitivity, and long sample preparation time. The oxidative stress of food and living organisms is measured using electrochemical methods [104,105], including cyclic voltammetry, differential pulse voltammetry, square wave voltammetry, and chronoamperometry [105]. The cyclic voltammetry method provides a wide range of information, such as the thermodynamics of the redox process and kinetics of heterogeneous electron transfer reactions [104].…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…The oxidative stress of food and living organisms is measured using electrochemical methods [104,105], including cyclic voltammetry, differential pulse voltammetry, square wave voltammetry, and chronoamperometry [105]. The cyclic voltammetry method provides a wide range of information, such as the thermodynamics of the redox process and kinetics of heterogeneous electron transfer reactions [104]. The differential pulse voltammetry also uses the same principle as the cyclic voltammetry method.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…In addition, the synergy of biologically produced substances can further increase their activity, especially in microbiostatic or microbicidal action according to the well-known theory of multiple barriers [ 90 ]. Therefore, the result of the optimized isolation with innovative “green” extraction method such as vacuum microwave assistance has been completed in previous studies [ 91 , 92 , 93 ] this research is focused in the use of these residues as animal feed. The proposed total utilization of the three solid residues by the food industry (Total Discharge approach) is a pioneer and can provide high value-added materials with low raw material costs.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are one of the largest groups of natural compounds which exhibit a broad range of biological activities including anti-oxidant, anti-inflammatory, anti-allergy, anti-viral, anti-cancer, anti-microbial, anti-mutagenic and cardio-protective effects directly related to the diverse structural configuration of these materials [ 4 ]. Numerous research reports in which polyphenols are reported have focused mainly on determination of the molecular profile of the compound derived from various plant extracts [ 5 , 6 ], determination of the biological activity [ 7 , 8 , 9 ] and the subsequent development and optimization of unique extraction methods for different plant metabolites [ 10 , 11 , 12 ]. However, current research is focused on enhancing the bioavailability and pharmacological properties of phenolic compounds in the human body for the purposes of targeted and improved therapy [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%